EPR spectra of deuterated methyl radicals trapped in low temperature matrices - Dmitriev, Yu.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
EPR spectra of CHD2, and CD3 radicals have been investigated in low-temperature matrices of H2, D2, and Ne at temperatures 1.6–4.2 K. A method of condensation from the gas phase on a cold substrate has been used. With decreasing sample temperature, a transformation of the shape of the CD3 spectrum in H2, D2, and Ne matrices and CHD2 spectrum in H2 and Ne was observed. This transformation was reversible in the above temperature range. The temperature effects are explained as reflecting a change in the populations of the lowest rotational states of the radicals. Based on the present data and known results for deuterated methyl radicals in Ar obtained in photolytic experiments, we compare the temperature behavior of the EPR spectra for the radicals trapped in various matrices. As a result an existence of a hindering barrier for the radical rotation is suggested.